Pengenalan Platform Digital Inovasi Kemasan dan Etika Hukum bagi Mahasiswa SMK Parung Panjang di Tangerang (Universitas Palangka Raya, 2026)
This article discusses an experiential training program that integrates three main pillars for students of Parung Panjang Vocational High School (SMK) in Tangerang: optimizing digital platforms as modern marketplaces, developing innovative product packaging to strengthen sales performance, and applying ethical and legal principles in digital business activities. The program is designed to prepare vocational students to become competent, creative, adaptive, and responsible young entrepreneurs in the digital economy. The implementation methods include project-based learning, workshops, seminars, product simulation, mentoring, and intensive practice in using online marketing media. Students are guided to identify market opportunities, design attractive packaging, promote products through digital channels, and understand consumer protection, intellectual property, and honest transaction practices. The expected outcomes include increased digital literacy, improved packaging design skills, stronger entrepreneurial motivation, and better awareness of business ethics and legal compliance. Overall, this program provides practical learning experiences that connect school-based entrepreneurship education with the demands of the contemporary business and industrial environment. It also encourages collaboration among teachers, students, and local business partners for sustainable vocational development in line with future workforce and innovation needs.